Changes in the Thickness of the Sublens Water Layer in Patients Using Scleral Lenses - O. I. Ryabenko; O. M. Selina; E. Yu. Kramarenko; O. O. Alyaeva (Oftalʹmologiâ, 2024)
Purpose of the study. To analyze the change in the thickness of the sublens water layer depending on the time of wearing lenses in patients using scleral lenses using the SkyOptix Laboratory lenses as an example.Patients and methods. To determine the thickness of the sublens water layer in the vertical and horizontal meridians, a study was performed in 33 people in 46 eyes. Among the patients there were 25 men and 8 women, from 18 to 59 years old (mean 37.3 ± 9.5 years). The main indication for the use of scleral lenses was the ineffectiveness of other methods of vision correction.Results. The mean sublens water layer thickness reduction in the total group of examined patients using scleral lenses was 9.3 % or 37.73 μm after 1 hour of wear and 20.8 % or 84.48 μm after 4 hours of wear compared to initial values.Conclusions. The largest and clinically significant changes in the thickness of the sublens water layer occur during the first hour of lens wear, which, according to our study, is approximately 40 microns. Considering the temporal dynamics of changes in the thickness of the sublens water layer, the final calculation of the parameters must be made no earlier than after 1 hour of wearing the scleral lens. The thickness of the sublens water layer should be assessed in relation to the time spent in the scleral lens. According to our survey, over the entire period of observation in all patients using scleral lenses, there is a decrease in the thickness of the sublens water layer over time of wearing, which requires further additional research to determine identifying the exact causes and factors underlying this process.